Unvaccinated child tetanus from nasal toy battery - Homola, Lukáš; Klučka, Josef; Helešic, Jan; Jirsenská, Zlata; Kratochvíl, Milan; Dominik, Petr; Urík, Milan; Horák, Ondřej; Jabandžiev, Petr; Krbková, Lenka; Štourač, Petr (Central European journal of public health, 2021)
We present the case report of an unvaccinated Czech child with tetanus. The child had not received any vaccines due to its parent's refusal. The disease originated from the wound in the nose caused by a small flat battery. The typical onset of tetanus followed after two weeks, rapidly progressing to respiratory failure with the need for mechanic ventilation despite intensive treatment. The child spent five weeks in the hospital. Mild long-term sequelae persisted 5 months.
Keywords: tetanus; Family; intensive care; Child; lidé; paediatric patient; Tetanus; rodina; Tetanus Toxoid; dítě; tetanový toxoid; Humans